Pengetahuan dan Kemampuan Guru Memanfaatkan Teknologi dalam Pembelajaran - Mukaromah, Hikmatul; Lutfiani, Dwi Isna (TSAQOFAH, 2024)
Education 4.0 is education characterized by the use of digital technology in the learning process or known as a cyber system. This system is able to make the learning process take place periodically without space and time limitations. Teachers are required to innovate and be able to learn in order to adapt their knowledge and abilities to the industry 4.0 era. This is caused by changing times followed by very rapid technological changes. Rapid change must be balanced by appropriate and reliable technology skills. Today's sophisticated technology makes it very easy for teachers to learn, therefore teachers are required to be able to utilize and use technology well, teachers must be able to keep up with the times because this has a big influence on the development of students in absorbing understanding of the material presented, technology Apart from having many uses, it also has many negative impacts on students if it is not used wisely. In research, the technique used is by searching for material related to the discussion in the article, both digitally and manually. After making references, then analyze the data, rearrange them starting from places and combine them with other words, make reductions or changes to words, and rearrange them according to what they are. The results of this research are a lack of knowledge and use of technology by students and teachers. The lack of use of technology by teachers is caused by the quantity and quality of teachers not being optimal. A teacher must be able to keep up with the rapid development of information and communication technology in utilizing these devices to support the material being taught. Meanwhile, students as actors in education should be able to make good use of technology but are actually lacking in the use of technology, students use it for things that are less useful because the generation takes formal education too lightly. This article also explains various ways to reduce the problem of teachers' and students' lack of knowledge in the use of technology.